The Effectiveness Comparison of Desloratadine and Loratadine in Reducing Total Nasal Symptom Score and the Level of Interleukin 4 in the Nasal Secretions of Allergic Rhinitis Patients - Luh Putu Dhena Purwaningsih1, Dwi Reno Pawarti1, Bakti Surarso1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Allergic rhinitis (AR) is a common atopic disease; however, the available therapy has limitation in the usage and its success rate. Desloratadine has a role as an alternative allergic rhinitis therapy to eliminate the overall symptoms of AR and reduce IL-4 level in nasal secretions. Method: This study was double-blind randomised clinical trial with pre-post test design. The data was analyzed by using independent sample t-test. There were 24 AR patients divided into 2 therapy groups which were study group (desloratadine) and control group (loratadine). The evaluation based on SGHT and IL-4 in nasal secretions was conducted pre and post 15 days of therapy. Results: The present study that was conducted on July-October 2016 showed significant difference in the average percentage of reduced TNSS in desloratadine group compared to loratadine group (p=0.000). The comparison of reduced level of IL-4 in nasal secretions between desloratadine and loratadine group was indicated insignificantly different. Conclusion: Reduced TNSS in desloratadine group was higher than in loratadine group. Also, there was no difference in decreased level of IL-4 in nasal secretions.